BOOK REVIEW of Modeling Economic Growth in Contemporary Slovakia - Paskal Zhelev (Bulgarian Journal of International Economics and Politics, 2025)
Augustín, M., Jančovič, P. and Sergi, B.S. (Eds.). (2025). Modeling Economic Growth in Contemporary Slovakia. Entrepreneurship and Global Economic Growth Series, Emerald Publishing Limited, Leeds, 264 pages. ISBN (print): 978-1-83549-455-4 This review examines the edited volume Modeling Economic Growth in Contemporary Slovakia (Emerald, 2025), which offers a comprehensive and empirically grounded assessment of Slovakia’s post-socialist economic transformation. The volume explores a range of interrelated themes, including trade and foreign direct investment, institutional reforms, regional disparities, innovation, and sectoral competitiveness. It presents a cohesive analysis of the country’s export-led, FDI-driven growth model and critically engages with its long-term sustainability in light of global economic shifts. The review evaluates the book’s methodological rigor, policy relevance, and interdisciplinary scope, while drawing parallels with Bulgaria’s own experience of EU integration. Overall, the volume stands as a valuable contribution to the literature on structural transformation, convergence, and economic policymaking in small, open economies in Central and Eastern Europe.